2019
DOI: 10.1177/0023677219862004
|View full text |Cite
|
Sign up to set email alerts
|

Nest-building performance in rats: impact of vendor, experience, and sex

Abstract: Nest building behavior has been intensely applied as a parameter for severity assessment in mice. In contrast, only a limited number of studies have reported nest building data from rats. Here, we assessed nest building in rats in two different facilities addressing the hypotheses that the vendor, previous experience with the nesting material as well as sex of the rats has an impact on the performance. Data from two study sites and three raters were compared to obtain information about the robustness of nest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Another difference became evident when analyzing nestbuilding behavior in kindled rats and mice with compromised nest-building only observed in rats [58]. The higher sensitivity of nest building in rats might be related to the lower level of motivation to construct complex nest structures [59]. Related to their smaller body size, thermoregulation in mice depends more intensely on environmental factors, so that it might be that nest building is only affected at higher levels of distress in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Another difference became evident when analyzing nestbuilding behavior in kindled rats and mice with compromised nest-building only observed in rats [58]. The higher sensitivity of nest building in rats might be related to the lower level of motivation to construct complex nest structures [59]. Related to their smaller body size, thermoregulation in mice depends more intensely on environmental factors, so that it might be that nest building is only affected at higher levels of distress in mice.…”
Section: Discussionmentioning
confidence: 99%
“…59 Therefore, again, standardization is crucial as assessment protocols may vary between laboratories, resulting in the lack or changed manifestation of these behaviours (Schwabe et al, this issue; Jirkof et al, this issue). 60,61 Another motivational-or emotionaldriven behaviour, namely voluntary wheel running, has been utilized to assess the severity of experimental procedures. 62 Benefits include an observer-independent, automatized assessment of severity that has been proposed to serve as an indicator of disturbed wellbeing (Mallien et al, this issue).…”
Section: Techniques To Assess Severity: Balancing Burden Bias and Bementioning
confidence: 99%
“…61 In another study, scoring of nesting behaviour as predefined in the respective SOP had to be optimized to enhance inter-rater reliability (Schwabe et al, this issue). 60 Furthermore, effects of predictability and adaptation to procedures as well as effects of the chronology of procedures have to be taken into account. Repeated predictable stress will cause resilience against colitis-induced behavioural changes in mice and behavioural changes associated with learned helplessness do not occur if the stressor is controllable.…”
Section: It All Comes Down To Study Designmentioning
confidence: 99%
“…Considering nest building activity in young mice, there are two relevant studies examining the ability of young mice to build nests which show diverging results: An earlier report from Moy et al (2004) found relevant levels of nest building activity in mice aged 3-4 weeks, while Eltokhi et al (2020) detected no relevant nesting behavior in adolescent mice. However, a range of interfering factors have to be considered when interpreting nesting data, among others, body weight, strain and housing conditions (Bult and Lynch, 1997;Martin et al, 2016;Robinson-Junker et al, 2017;Schwabe et al, 2020). Considering burrowing activity, earlier studies indicated relevant burrowing activity in adolescent mice (Hart et al, 2012;McLinden et al, 2012;Eltokhi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%